ChemInform Abstract: Methylaluminoxane (MAO)‐Assisted Direct Amidation of Esters. Issue 27 (18th June 2015) - Desrat, Sandy; Ducousso, Aline; Gapil, Shelly; Remeur, Camille; Roussi, Fanny
Abstract The reaction is performed starting from alkanoates, alkenoates, and benzoates with the corresponding methyl carboxylates providing the highest product yields.